Measurement of the influence of titanium hip prosthesis on therapeutic electron beam dose distributions in a novel pelvic phantom. (October 2017) - Ade, Nicholas; du Plessis, F.C.P.
Highlights: A novel Nylon-12 pelvic phantom with an in-built hip Ti prosthesis is presented. Measured dose distortions with film increased with electron energy and field size. The perturbations increased to values of 21% and 23% for 18 and 22 MeV electrons. XiO TPS pencil beam algorithm inaccurately predicted the effects of the prosthesis. Comparison of film and TPS dose data for 18 and 22 MeV gave errors of 22% and 28%. Abstract: Purpose: To investigate the degree of 18 and 22 MeV electron beam dose perturbations caused by unilateral hip titanium (Ti) prosthesis. Methods: Measurements were acquired using Gafchromic EBT2 film in a novel pelvic phantom made out of Nylon-12 slices in which a Ti-prosthesis is embedded. Dose perturbations were measured and compared using depth doses for 8 × 8, 10 × 10 and 11 × 11 cm 2 applicator-defined field sizes at 95 cm source-surface-distance (SSD). Comparisons were also made between film data at 100 cm SSD for a 10 × 10 cm 2 field and dose calculations made on CMS XiO treatment planning system utilizing the pencil beam algorithm. The extent of dose deviations caused by the Ti prosthesis based on film data was quantified through the dose enhancement factor (DEF), defined as the ratio of the dose influenced by the prosthesis and the unchanged beam. Results: At the interface between Nylon-12 and the Ti implant on the prosthesis entrance side, the dose increased to values of 21 ± 1% and 23 ± 1% for 18 and 22 MeV electron beams, respectively. DEFs increased with increasing electron energy and field size, and were found to fall off quickly with distance from the nylon-prosthesis interface. A comparison of film and XiO depth dose data for 18 and 22 MeV gave relative errors of 20% and 25%, respectively. Conclusion: This study outlines the lack of accuracy of the XiO TPS for electron planning in highly heterogeneous media. So a dosimetric error of 20–25% could influence clinical outcome.